Determination of energy usage and potential environment impact (pei) of a multi effect distillation system for production of water for injection (wfi) in pharmaceutical industries - Nur Mahirah, Hibrahim (2014)
Pharmaceuticals are emerging as a rapidly growing global industry because health is a crucially important social and economic asset whilst the cornerstone for human development. Energy in pharmaceutical industries is used to operate the unit operations and also needed to produce water for injection (WFI) as production utilities. Significantly, WFI is largely used in pharmaceutical processes. Typical process for generating WFI is through a multi effect distillation which needs temperature and therefore uses large amount of energy. The high energy consumption increase the amount of greenhouse gases in the atmosphere particularly carbon dioxide, methane and nitrous oxide. As the pharmaceutical industry expands, the industry faced more serious environmental problems arising from increasing global production. Thus aware of this fact, it is important to assess the energy consumption and its environmental impact as early as possible especially during the process design stage to avoid further harm to the future generation to meet their needs. In order to know the emission of mass and energy would emit to environmental, we used the waste reduction (WAR) algorithm methodology analysis to access the energy usage in process which is potential environmental impact (PEI) and economic impact. In this work, we used Super Pro software to gain the amount of energy used for the WFI production in pharmaceutical industry. Furthermore, the data from the research can be analysis to achieve the sustainable development of process without sacrificed our worth earth. The total energy demand is 95.29 kWh was calculated to produce 880 L/hr WFI in pharmaceutical industry. The energy produced from several equipment such as listed above. Result from the PEI value calculation suggested that the higher amount of component emission is 122 CO2 contain